Noninvasive Ventilation for Patients with Hypoxemic Acute Respiratory Failure - Brochard, Laurent; Lefebvre, Jean-Claude; Cordioli, Ricardo Luiz; Akoumianaki, Evangelia; Richard, Jean-Christophe M. (Seminars in Respiratory and Critical Care Medicine, 2014)
Noninvasive ventilation (NIV) has an established efficacy to improve gas exchange and reduce the work of breathing in patients with hypoxemic acute respiratory failure. The clinical efficacy in terms of meaningful outcome is less clear and depends very much on patient selection and assessment of the risks of the technique. The potential risks include an insufficient reduction of the oxygen consumption of the respiratory muscles in case of shock, an excessive increase in tidal volume in case of lung injury, and a risk of delayed or emergent intubation. With a careful selection of patients and a rapid decision regarding the need for intubation in case of failure, great benefits can be offered to patients. Emerging indications include its use in patients with treatment limitations, in the postoperative period, and in patients with immunosuppression. This last indication will necessitate reappraisal because the prognosis of the conditions associated with immunosuppression has improved over the years. In all cases, there is both a time window and a severity window for NIV to work, after which delaying endotracheal intubation may worsen outcome. The preventive use of NIV seems promising in this setting but needs more research. An emerging interesting new option is the use of high flow humidified oxygen, which seems to be intermediate between oxygen alone and NIV.
Keywords: mechanical ventilation; continuous positive airway pressure; hypoxemia; gas exchange; acute lung injury; acute respiratory distress syndrome